6 Unravelling the mechanisms of mental stress vs exercise induced myocardial ischaemia. (24th April 2016) - Arri, SS; Williams, R; Asrress, K; Lumley, M; Ellis, H; Patterson, T; Khawaja, MZ; Cooke, R; Perera, D; Coutts, J; Clapp, B; Marber, M; et al.
Abstract : Background: Mental stress (MS) triggers myocardial ischaemia at cardiac workloads that are lower than those that cause exercise-induced ischaemia in the same patient. Methods: Intracoronary pressure and flow velocity data were acquired from 15 CAD (FFR <0.8 and/or >70% stenosis) patients and 11 controls during MS (mental arithmetic, stroop test). 7 CAD patients and 5 controls also underwent cycle ergometer exercise stress (ES). Coronary flow average peak velocity (APV), microvascular resistance (MR) and Buckberg index (BI) were calculated. Results: At peak MS rate pressure product (RPP), a marker of myocardial oxygen demand, increased by 4418 ± 2353mmHg.bpm (p = 0 <0001). Despite this there was no increase in coronary flow but instead a paradoxical rise in MR (p = 0.01) and a fall in the BI (p < 0.001), a surrogate for subendocardial ischaemia. Interestingly wave free MR, more reflective of vascular tone and less affected by the contractile forces of the ventricle, did not increase during RPP matched ES (see Figure 1 ). In contrast an increase in coronary flow predominantly driven by the forward compression and backward expansion waves was observed in the control group (p = 0.001). Conclusion: A paradoxical rise in MR does occur in response to MS that is not seen with ES at similar workloads. This abnormal endothelial response correlates with the extent of atherosclerosis in the vessel.